Un premier point de vue juridique - Caron, Madeleine (Assurances)

(untitled) (HEC Montréal, 1988)
Mrs. Caron, lawyer, presents today's opinion on AIDS, insurance and the law: the role of the Human Rights Commission and the Quebec Charter of Rights. More precisely, does Article 12 of the Charter oblige the insurer to provide insurance? Can the insurer exclude AIDS as a risk from all his policies? What problems are there in applying the Charter, where insurance policies are concerned? The author's well-phrased comments give us not only answers to these questions, but also her thoughts on approaches to basic human rights and the rights of insurance companies.